Quaternion generic Fourier descriptor for color object recognition. Issue 12 (December 2015) - Li, Heng; Liu, Zhiwen; Huang, Yali; Shi, Yonggang
Abstract: By introducing quaternions, Fourier transforms, the fundamental tool in signal and image processing, were extended to treat a color image in a holistic manner. On the other hand, color image description has long been a major topic of pattern recognition. In this work, inspired by the quaternion Fourier transforms, we propose a quaternion generic Fourier descriptor to describe color images holistically and effectively without losing any color information. The theoretical framework to construct a set of invariants with respect to geometric transformation is also provided. Moreover, several experiments are conducted on color image databases to illustrate the effectiveness of the proposed invariants. The results provide supports for that the quaternion generic Fourier descriptor invariants have striking robustness to geometric transformation and noise. Remarkable progress in accuracy, robustness and efficiency of color object recognition has been made by the proposed descriptor. In addition, it presents superior performances on real recognition scenarios. Abstract : Highlights: We propose an image descriptor with the quaternion algebra to describe color images. A framework to develop robust invariants to geometric transformation is provided. Experiments are conducted to validate the performance of the proposed descriptor. The proposed descriptor performs robustly to geometric transformation and noise. A progress in accuracy of recognition has been made by the proposed descriptor. On real recognition scenarios, the proposed descriptor also performs superiorly.